The introduction of mandatory CPD for newly state registered diagnostic radiographers: An Irish perspective. Issue 2 (May 2018) - Grehan, J.; Butler, M.-L.; Last, J.; Rainford, L.
Abstract: Introduction: Irish diagnostic radiography has undergone significant change with the dual introduction of state registration and mandatory Continuing Professional Development (CPD) in October 2015. We aimed to investigate motivators and barriers around CPD participation, mechanisms of CPD delivery and confidence of radiographers in using e-learning. Methods: A questionnaire distributed nationally during this period captured Radiographer opinion through the use of closed and open questions. The questionnaire was distributed in hard copy and online formats depending on site preference. Results: 71% of centres participated, rendering 453 responses in total from a possible 1222 respondents employed in those sites at the time of the survey. A varied range of ages and post qualification experience were represented. Respondents indicated use of several CPD options with the majority considering CPD to be important, very important or critical. Social media as a mechanism of CPD delivery was considered acceptable by 48%, while online learning elicited responses ranging from not confident to absolutely confident. Top motivators for CPD activity included interest, developing new knowledge and competency. Principal barriers included funding, time allocation and location issues. Conclusion: This study identified Radiographer desire to undertake CPD and the need for developing online CPD offerings. An overall positive perception towards CPD was noted however barriers were identified which require specific redress strategies. Highlights: CPD was considered important, very important or critical to respondents. Half of respondents less than very confident with using online learning. Top motivators for CPD were interest, knowledge and competency. Top barriers for CPD were funding, time and location. Irish radiographers want CPD and further flexible CPD offerings are needed.